2022
DOI: 10.1111/jfbc.14451
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective potential of Moringa oleifera mediated by NF‐kB/Nrf2/HO‐1 signaling pathway: A review

Abstract: Moringa oleifera is a traditional Indian herb belonging to the Moringaceae family, it is commonly known as the horse‐radish tree, drumstick, or sahajna. In developing countries, Moringa is used as feed for both humans and animals due to its well‐known antioxidant, anti‐inflammatory, and anti‐apoptotic properties owing to its several phytoconstituents including β‐carotene, quercetin, kaempferol, ascorbic acid, flavonoids, phenolic acid, rhamnose, glycosylates, glucomoringin, and isothiocyanates. These constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 121 publications
0
12
0
Order By: Relevance
“…MO attenuated ARV toxicity by upregulating the expression of NRF2 and its related antioxidants. This effect was previously demonstrated at the transcriptional and translational levels in various cell lines, including HepG2, HK-2, and V79-MZ cells, as well as animal models [ 97 , 98 , 99 ], C2C12 skeletal muscle cells [ 100 ] as well as in rat kidneys [ 101 , 102 ] and rat liver tissues [ 103 , 104 ]. MO contains several bioactive compounds, such as quercetin glucosinolates, isothiocyanate, flavonoids, and phenolic acids, that have been found to activate the NRF2-ARE [ 36 , 99 , 105 ].…”
Section: Discussionmentioning
confidence: 71%
“…MO attenuated ARV toxicity by upregulating the expression of NRF2 and its related antioxidants. This effect was previously demonstrated at the transcriptional and translational levels in various cell lines, including HepG2, HK-2, and V79-MZ cells, as well as animal models [ 97 , 98 , 99 ], C2C12 skeletal muscle cells [ 100 ] as well as in rat kidneys [ 101 , 102 ] and rat liver tissues [ 103 , 104 ]. MO contains several bioactive compounds, such as quercetin glucosinolates, isothiocyanate, flavonoids, and phenolic acids, that have been found to activate the NRF2-ARE [ 36 , 99 , 105 ].…”
Section: Discussionmentioning
confidence: 71%
“…Research has indicated that MO contains numerous bioactive compounds that have favorable impacts on human health. 18,19 The data obtained in this study after in silico docking analysis hence suggested that the bioactive compounds present in the MO leaf extract could potentially inhibit the over-activated PARP1 protein.…”
Section: Discussionmentioning
confidence: 73%
“…Research has indicated that MO contains numerous bioactive compounds that have favorable impacts on human health. 18, 19…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that many nutraceuticals, such as quercetin, avonoids, ascorbic acid, βcarotene, and phenolic acid, have neuroprotective effects and may alleviate the symptoms of PD [17,18]. This study investigated the effects of CA on the MPTP-induced zebra sh PD model.…”
Section: Discussionmentioning
confidence: 99%